2015
DOI: 10.1021/acs.molpharmaceut.5b00069
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin-BF, a Novel Antimicrobial Peptide from Bungarus fasciatus, Attenuates Disease in a Dextran Sulfate Sodium Model of Colitis

Abstract: Antimicrobial peptides are molecules of innate immunity. Cathelicidin-BF is the first cathelicidin peptide found in reptiles. However, the immunoregulatory and epithelial barrier protective properties of C-BF have not been reported. Inflammatory bowel diseases, including ulcerative colitis and Crohn's disease, can lead to colon cancer, the third most common malignant tumor. The objective is to develop the new found cathelicidin-BF as a therapeutic to patients of ulcerative colitis. The morphology of the colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 64 publications
7
42
0
Order By: Relevance
“…Differences were determined via a one-way ANOVA followed by a Duncan multiple range test. # p , 0.05 compared with control, *p , 0.05. with this finding, previous studies have shown that antimicrobial peptides such as porcine b defensin 2 and Cathelicidin-BF attenuate the DSS-induced disruption of mucin expression in the intestine of mice (3,14). These data suggest that CWA modulates goblet cell function and MUC-2 production in the intestine.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Differences were determined via a one-way ANOVA followed by a Duncan multiple range test. # p , 0.05 compared with control, *p , 0.05. with this finding, previous studies have shown that antimicrobial peptides such as porcine b defensin 2 and Cathelicidin-BF attenuate the DSS-induced disruption of mucin expression in the intestine of mice (3,14). These data suggest that CWA modulates goblet cell function and MUC-2 production in the intestine.…”
Section: Discussionsupporting
confidence: 70%
“…Bacteria do not easily develop resistance against antimicrobial peptides because of the membrane-disrupting mechanisms of these molecules (13). Cathelicidin peptides, one family of antimicrobial peptides, not only exhibit antimicrobial activities (14) but they also function as immune regulators, thereby modulating immune responses in the host (12,15). For instance, LL-37 attracts T cells, neutrophils, mast cells, and macrophages and modulates LPSinduced inflammation by binding to LPS or directly perturbing the MyD88 signaling pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that antibiotics therapy with the combined dose of ampicillin, metronidazole, neomycin and vancomycin, or bacitracin and neomycin, increases bacterial translocation, induces mild inflammation and the risk of developing DSS‐induced colitis 65 , 66 . However, different studies using CIN‐102, a natural cinnamon oil composition‐like mixture with broad‐spectrum antibacterial activity, and cathelicidin from Bungarus fasciatus decreased intestinal bacterial load, and improved symptoms of DSS‐induced colitis 67 , 68 . Ciprofloxacin and metronidazole have also been shown to reduce ileitis in genetically modified mice through the downregulation of pro‐inflammatory cytokines IFN‐γ and TNF, and T‐cell activation 69 .…”
Section: The Local Effects Of Gut Microbiota On Ibdmentioning
confidence: 99%
“…65,66 However, different studies using CIN-102, a natural cinnamon oil composition-like mixture with broad-spectrum antibacterial activity, and cathelicidin from Bungarus fasciatus decreased intestinal bacterial load, and improved symptoms of DSS-induced colitis. 67,68 Ciprofloxacin and metronidazole have also been shown to reduce ileitis in genetically modified mice through the downregulation of pro-inflammatory cytokines IFN-γ and TNF, and T-cell activation. 69 Although some antibiotics such as ampicillin and ciprofloxacin have broad-spectrum activities, others have specific activities, with vancomycin targeting Gram-positive bacteria, and metronidazole targeting anaerobes.…”
Section: The Local Effects Of Gut Microbiota On Ibdmentioning
confidence: 99%